Metal-organic frameworks as high-potential adsorbents for liquid-phase separations of olefins, alkylnaphthalenes and dichlorobenzenes - Alaerts, Luc; Maes, Michael; van der Veen, Monique A; Jacobs, Pierre A; De Vos, Dirk E (Physical chemistry chemical physics : PCCP, 2009)
Three metal-organic frameworks (MOFs) with similar pore window diameters, [Cu(3)(BTC)(2)], MIL-47 and MIL-53(Al), are tested for adsorption of olefins, alkylnaphthalenes and dichlorobenzenes in the liquid phase. Selective adsorption of olefins is possible only on [Cu(3)(BTC)(2)] viapi-complexation on its open metal sites. This material shows a remarkable preference for cis-olefins over trans-olefins. All three MOFs have high affinities for alkylnaphthalene and dichlorobenzene isomers. Separation of 1,4-dimethylnaphthalene from other alkylnaphthalene isomers and of p- and m-dichlorobenzene can be carried out on both MIL-47 and MIL-53(Al), as shown with breakthrough experiments. For the alkylnaphthalenes, column experiments at different concentrations point to enthalpic interactions as important factors determining selectivity, and the occurrence of steric effects during the adsorption of 1,4-dimethylnaphthalene shows that its kinetic diameter approaches the pore diameter of the adsorbents. For the dichlorobenzenes, packing effects dominate the adsorption selectivity.